Qualitative Assessments via Infrared Vision of Sub-surface Defects Present Beneath Decorative Surface Coatings; International Journal of Thermophysics; Vol. 39, iss. 1 - Sfarra S. Stefano; Fernandes H. C. Henrique Coelho; Lopez F. Fernando; Ibarra-Castanedo C. Clemente; Zhang H.; Maldague X. Xavier (2018, 2018)
Title screen